Methods of building language knowledge through online testing systems - Komilova, Zulhumor Khakimovna; Yuldasheva, Muqaddaskhon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article provides an in-depth exploration of modern approaches to assessing language proficiency through online testing systems. With the rapid expansion of digital technologies, language learning and assessment have shifted from traditional formats to fast, transparent, and automated methods. The paper discusses the functional features of online testing platforms, adaptive testing models, automated scoring mechanisms, user performance tracking tools, and data-driven result analysis algorithms. Additionally, it examines issues such as test reliability, validity, difficulty level calibration, reduction of technical errors, and the promotion of academic integrity in digital environments.